2008
DOI: 10.2465/jmps.071220
|View full text |Cite
|
Sign up to set email alerts
|

Epidote-(Sr), CaSrAl2Fe3+(Si2O7)(SiO4)(OH), a new mineral from the Ananai mine, Kochi Prefecture, Japan

Abstract: Epidote -(Sr), CaSrAl 2 Fe 3+ (Si 2 O 7 )(SiO 4 )(OH), the Sr -analog of epidote, was found in the Nagakawara and Hohnomori deposits at the Ananai mine, Kochi Prefecture, Japan. It occurs in the form of prismatic crystals up to 1 cm in length in the tinzenite veins or the fine crystal aggregates in piemontite breccia. Epidote -(Sr) is optically biaxial negative, α = 1.737(2), β = 1.780 (2), γ = 1.792 (2), and 2V calc = 62° and has perfect cleavage parallel to {001}. It exhibits pleochroism-X: pale greenish yel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Eu REE Fig. 23 Fujinaga et al, 2006bMinakawa et al 2008Sr Nakamura 1990 Type A Fujinaga et al, 2006b). REE data of PAAS and TAG (Trans-Atlantic Geotraverse hydrothermal field) hydrothermal fluids are from Taylor and McLenann (1985) and Mitra et al (1994), respectively.…”
Section: Cementioning
confidence: 99%
“…Eu REE Fig. 23 Fujinaga et al, 2006bMinakawa et al 2008Sr Nakamura 1990 Type A Fujinaga et al, 2006b). REE data of PAAS and TAG (Trans-Atlantic Geotraverse hydrothermal field) hydrothermal fluids are from Taylor and McLenann (1985) and Mitra et al (1994), respectively.…”
Section: Cementioning
confidence: 99%
“…Dörsam et al (2007) synthesized strontium-bearing clinozoisite in the compositional range Sr/(Ca + Sr) = 0.078 to 0.51; they showed that strontium partitions into the larger A2 site and that significant strontium incorporation at the A1 site occurs only for Sr/(Ca + Sr) >0.45. Minagawa et al (2008) reported that epidote-(Sr) also has a strong site preference for strontium in the A2 site with A2 (Sr/Ca) / A1 (Sr/Ca)~147. Thus, the assumption that strontium is fully ordered in the A2 sites is a reasonable simplification for discussing the epidote composition of the Kurosegawa samples, i.e.…”
Section: Bulk-rock Compositionsmentioning
confidence: 99%
“…Strontium-rich epidote has been reported from a variety of metamorphic rocks including metasediments of greenschist facies in New Zealand (Grapes and Watanabe, 1984); eclogite in the Bjørkedalen peridotite from the Western Gneiss Region, Norway (Brastad, 1985); metabasite in serpentinite from Guatemala (Harlow, 1994); ultrahigh-pressure (UHP) eclogites from the Su-Lu belt, China (Nagasaki and Enami, 1998); prehnite rock in the serpentinite mélange from the Itoigawa-Ohmi District, Japan (Miyajima et al, 2003); a carbonatite skarn from the Canary Islands, Spain (Ahijado et al, 2005); and the manganese-ore deposits in the Ananai mine, Kochi, Japan (Minagawa et al, 2008). Three types of models have been proposed for the formation of strontium-rich epidote.…”
Section: Formation Of Strontium-rich Epidotementioning
confidence: 99%
“…and T is tetrahedral sites (Armbruster et al 2002;Mills et al, 2009). Epidote-group minerals of epidote-supergroup, such as clinozoisite, epidote and piemontite, are important Sr containers in metamorphic rocks (e.g., Grapes and Watanabe, 1984;Mottana, 1986;Reinecke, 1986;Nagasaki and Enami, 1998;Enami, 1999;Miyajima et al, 2003;Nagashima et al, 2006), metamorphosed manganese ore deposits (e.g., Kato and Matsubara, 1986;Bonazzi et al, 1990;Perseil, 1990;Minakawa, 1992;Nagashima et al, 2007;Minakawa et al, 2008; A d v a n c e P u b l i c a t i o n A r t i c l e al., 2010), and metamorphosed manganiferous iron ore deposits (Akasaka et al, 1988;Togari et al, 1988). Thus, the occurrence and crystal chemical properties of Sr-bearing epidote-group minerals, such as solubility of Sr and its effect on the Mn and Fe contents and crystal structure, have been interested in.…”
Section: Introductionmentioning
confidence: 99%